Emission of dark envelops in a fiber ring laser with net normal cavity dispersion - Shen, Huang (2018)
We report on a novel state of dark pulse emission in a net normal dispersion cavity fiber ring laser. We show both experimentally and numerically that the observed dark pulses are dark envelops formed as a result of the superposition between a high repetition rate dark pulse train and dark solitons formed in the fiber laser.